Oliver Twist - Dickens Charles; Polanski, Roman; Benmussa, Robert; Sarde, Alain, 1952-; Harwood, Ronald, 1934-; Kingsley, Ben, 1943-; Clark, Barney; Foreman, Jamie, 1958-; Dickens, Charles, 1812-1870.; Tri-Star Pictures; R.P. Productions; Runteam Ltd.; et al. (London : Random, 2007)
After living in poor conditions, Oliver runs away to the streets of London, where he meets a gang of pickpockets. Soon his life is changed forever.
Copyright Claimant: Oliver Twist Productions, LLP. Previous Registration: Screenplay, prev. pub. music and recordings. Basis of Claim: NM: entire motion picture except material prev. pub., and screenplay. Date of Creation: 2005; Date of Publication: 2005-09-23; Registration Number / Date: PA0001267146 / 2005-09-23.
Summary adapted from FirstSearch, OCLC 62287043, viewed Apr. 23, 2008.
Based on the novel Oliver Twist by Charles Dickens.
Not viewed.
Sources used: copyright data sheet; copyright database; Variety Web site, review posted Sept. 11, 2005, viewed Apr. 23, 2008; Internet movie database, viewed Apr. 23, 2008; FirstSearch, OCLC 62287043, viewed Apr. 23, 2008.
Executive producers, Timothy Burrill, Petr Moravec ; camera, Pawel Edelman ; editing, Herve de Luze ; music, Rachel Portman.
Keywords: Orphans -- Drama; Pickpockets -- Drama; Film adaptations; Melodramas (Motion pictures); Fiction films